2001
DOI: 10.1136/bjsm.35.1.43
|View full text |Cite
|
Sign up to set email alerts
|

The association football medical research programme: an audit of injuries in professional football

Abstract: Objectives-To undertake a prospective epidemiological study of the injuries sustained in English professional football over two competitive seasons. Methods-Player injuries were annotated by club medical staV at 91 professional football clubs. A specific injury audit questionnaire was used together with a weekly form that documented each club's current injury status. Results-A total of 6030 injuries were reported over the two seasons with an average of 1.3 injuries per player per season. The mean (SD) number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

68
608
14
85

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 640 publications
(775 citation statements)
references
References 18 publications
68
608
14
85
Order By: Relevance
“…Repeated SSC exercise performed over a prolonged period of time is likely to lead to modified musculotendon unit behaviour, altered stiffness regulation, impaired function and reduced dynamic knee stability (McLean et al 2007;Nicol et al 2006). Fatigue during soccer has been associated with increased injury risk in adult (Hawkins et al 2001) and youth football (Price et al 2004). It has been speculated that altered leg stiffness and movement control during a soccer-match contributes to the increased injury risk associated with fatigue (Cone et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated SSC exercise performed over a prolonged period of time is likely to lead to modified musculotendon unit behaviour, altered stiffness regulation, impaired function and reduced dynamic knee stability (McLean et al 2007;Nicol et al 2006). Fatigue during soccer has been associated with increased injury risk in adult (Hawkins et al 2001) and youth football (Price et al 2004). It has been speculated that altered leg stiffness and movement control during a soccer-match contributes to the increased injury risk associated with fatigue (Cone et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The age used for inclusion was 16 years, as adult teams often include players of this age [8,[38][39][40][41]. This is also in accordance with the FIFA Laws of the Game, which are rules for players aged 16 and over and may be adjusted for those under 16 [37].…”
Section: Participantsmentioning
confidence: 99%
“…Hamstring strains are one of the most common injuries at professional football clubs, accounting for 12-16% of all injuries [5,39,58,59]. It is believed that they often occur during rapid eccentric loading when they are stretched beyond the optimal torque for generating tension, notably during sprinting [52,58,60].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…It is reported that 77-83% of all ankle sprains are focal to the lateral ligament complex (Hawkins et al, 2001;Price et al, 2004;Woods et al, 2003), with excessive loading during inversion and plantar flexion the most common mechanism of injury (Ferran & Maffulli, 2006;Kaminski et al, 2013). When the foot is forced into a compromised position, the mechanoreceptors in the ankle ligaments and joint capsule sense the extreme or sudden movements and initiate a dynamic restraint (Hertel, 2002;Konradsen et al, 1997;Hertel, 2000;Jackson et al, 2009;Michelson & Hutchins, 1995).…”
Section: Introductionmentioning
confidence: 99%